Preoperative medical therapy for acromegaly: current knowledge and clinical significance - He, Dan; Wang, Qinyi; Sheng, Zhifeng; Li, Guohua (Frontiers in Endocrinology, 2026)
Acromegaly is a chronic endocrine disorder characterized by excessive secretion of growth hormone (GH), predominantly caused by pituitary adenomas. Despite advancements in neurosurgical techniques, the surgical remission rates for invasive macroadenomas or giant adenomas remain unsatisfactory. Therefore, multimodal treatment strategies, including preoperative medical therapy (POMT), have been implemented to improve patient outcomes. Among these, first-generation somatostatin receptor ligands (fg-SRLs) have been the most extensively studied preoperative agents; however, their clinical efficacy in enhancing postoperative remission remains controversial. In recent decades, ongoing research into novel drugs and molecular targets are reshaping the therapeutic landscape of POMT. Beyond traditional clinical models and functional assays, the integration of advanced imaging modalities and molecular biomarkers promises to refine patient stratification, particularly for individuals with suboptimal responses to transsphenoidal surgery (TSS). Furthermore, novel SRL formulations and the identification of new molecular targets could further expand the therapeutic landscape of POMT. In this narrative review, we systematically summarize the latest research advancements in POMT for acromegaly and discusses potential therapeutic strategies and persisting obstacles in this field.